البيئة الملائمة لجذب الاستثمارات الأجنبية المباشرة للاقتصاد السوري - محمود يوسف عبد العزيز (Latakia University Journal - Economic and Legal Sciences Series, 2019)
نتيجة لتزايد أهمية تدفقات الاستثمار الأجنبي المباشر خاصة بالنسبة للدول النامية؛ حيث يعد أحد أهم محددات التنمية والنمو الاقتصادي، تعمل معظم الدول على خلق مناخ مناسب لجذب الاستثمارات. لذلك تمثل الهدف الأساسي لهذه الدراسة بالتعرف على أهم المشاكل التي تعوق تدفق الاستثمار الأجنبي المباشر بالإضافة إلى التعرف على أهم السياسات التي تساعد على جذب الاستثمارات الأجنبية المباشرة إلى سورية. As a result of the increasing importance of foreign direct investment flows, especially for developing countries; where is one of the most important determinants of economic growth and development, working most of the States to create an appropriate atmosphere to attract investment. Therefore, a primary objective of this study identify the most important problems that hamper the flow of foreign direct investment as well as identify the most important policies that help to attract foreign direct investment to Syria.